Dan Stuart's fistic carnival - Miletich, Leo N. (Texas A & M University Press, 1994)
"Never have so many done so much to stop so few. The year was 1895, and Dallas gambler Dan Stuart had a modest idea: promote a boxing carnival featuring a match for the heavyweight championship of the world between Gentleman Jim Corbett and Fighting Bob Fitzsimmons. What could be simpler?" "This richly detailed true epic of a fight and the hard-punching (and sometimes loony) political and religious turmoil surrounding it will entertain not only sports fans but all who appreciate a well-told tale that demonstrates once and for all that truth can be stranger than fiction - a lot stranger."--Jacket.